1999
DOI: 10.1073/pnas.96.14.7894
|View full text |Cite
|
Sign up to set email alerts
|

Atomic levers control pyranose ring conformations

Abstract: Atomic force microscope manipulations of single polysaccharide molecules have recently expanded conformational chemistry to include force-driven transitions between the chair and boat conformers of the pyranose ring structure. We now expand these observations to include chair inversion, a common phenomenon in the conformational chemistry of six-membered ring molecules. We demonstrate that by stretching single pectin molecules (1 3 4-linked ␣-D-galactouronic acid polymer), we could change the pyranose ring conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
167
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 27 publications
12
167
1
Order By: Relevance
“…These in vivo systems are complex and very different from the idealized systems presented in previous polysaccharide forcespectroscopy studies (52,53). In an artificial system, the concentration of polysaccharide on a surface can be precisely controlled so that only one polysaccharide filament can be pulled for each force-spectroscopy measurement.…”
Section: In Vivo Force Spectroscopy Of Extracellular Fibrils On the Mmentioning
confidence: 99%
“…These in vivo systems are complex and very different from the idealized systems presented in previous polysaccharide forcespectroscopy studies (52,53). In an artificial system, the concentration of polysaccharide on a surface can be precisely controlled so that only one polysaccharide filament can be pulled for each force-spectroscopy measurement.…”
Section: In Vivo Force Spectroscopy Of Extracellular Fibrils On the Mmentioning
confidence: 99%
“…In the most typical atomic force microscopy (AFM) experiment, a single molecule adsorbed between a substrate and the cantilever tip is extended vertically at a constant rate while the resulting force is measured (2)(3)(4)(5)(6)(7)(8)(9)(10). Although it may seem that these experiments can be completed equally by controlling either the extension or the force applied to the molecule, these two modes can yield quite different results (e.g., see ref.…”
mentioning
confidence: 99%
“…Our experiments enhance the ability of single-molecule force spectroscopy to make high-resolution measurements of the conformations of single polysaccharide molecules under a stretching force, making an important addition to polysaccharide spectroscopy. S ingle molecule force spectroscopy has become an important tool to examine the conformations of proteins and polysaccharide molecules under a stretching force (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Recent experiments have demonstrated that a force field can trigger conformational changes in these molecules that cannot be observed by traditional NMR or x-ray crystallographic techniques.…”
mentioning
confidence: 99%
See 2 more Smart Citations